Pengaruh Temperatur Lingkungan Terhadap Kinerja AC Split 1 PK dengan Refrigerant R32 dan Brezon - edi pujianto; Selamet Saefudin; Purnomo; Muhammad Ragil Febryan; Rizka Noor Miftakhul Ulum (Universitas Wahid Hasyim, 2025)
Air conditioners (AC) are among the most widely used appliances in tropical countries such as Indonesia. However, high energy consumption and the use of refrigerants with high Global Warming Potential (GWP) pose major challenges to energy and environmental sustainability. This study aims to analyze and compare the thermodynamic performance of two types of refrigerants, namely R-32 and Breezon MC32 (R-1270), in a vapor-compression refrigeration system. Performance tests were conducted under varying ambient temperatures (28 °C, 31 °C, and 34 °C) and evaporator loads (19 °C, 22 °C, 25 °C, 28 °C). The main parameters analyzed include power consumption, compression work, mass flow rate, compressor power, heat rejection, refrigeration effect, cooling capacity, and Coefficient of Performance (COP). The results show that Breezon MC32 with a 90% charge mass achieves a higher COP and lower power consumption compared to R-32 with a 100% charge, particularly under high ambient temperature conditions. This demonstrates the potential of Breezon MC32 as a more environmentally friendly and energy-efficient alternative refrigerant. Keywords: cooling capacity, power consumption, COP, R-32, Breezon